The expanding roles of long non-coding RNAs in the regulation of cancer stem cells. (March 2019) - Ma, Zhaowu; Wang, Ying-Ying; Xin, Hong-Wu; Wang, Lingzhi; Arfuso, Frank; Dharmarajan, Arunasalam; Kumar, Alan Prem; Wang, Hong; Tang, Feng Ru; Warrier, Sudha; Tergaonkar, Vinay; Sethi, Gautam
Abstract: Long non-coding RNAs (lncRNAs) are a novel class of gene regulators playing multifaceted roles in physiological processes as well as pathological conditions such as cancer. Cancer stem cells (CSCs) are a small subset of tumor cells that constitute the origin and development of various malignant tumors. CSCs have been identified in a wide spectrum of human tumors and could act as a critical link underlying the processes of tumor metastasis and recurrence. Mounting evidence indicates that lncRNAs are aberrantly expressed in diverse CSCs and regulate CSC properties at different molecular levels. Here, we very briefly summarize the recent findings on the potential roles of lncRNAs in regulating various functions of CSCs, and elaborate on how can lncRNAs impact CSC properties via interacting with other macromolecules at the epigenetic, transcriptional, and post-transcriptional levels. This mini-review also highlights the understanding of the modular regulatory principles of lncRNA interactions in CSCs.